Modeling population growth and site specific control of the invasive Lantana camara L. (Verbenaceae) under differing fire regimes. Issue 2 (12th March 2013) - Osunkoya, Olusegun O.; Perrett, Christine; Fernando, Chandima; Clark, Cameron; Raghu, Sathyamurthy
Abstract: It is at the population level that an invasion either fails or succeeds. Lantana camara L. (Verbenaceae) is a weed of great significance in Queensland Australia and globally but its whole life‐history ecology is poorly known. Here we used 3 years of field data across four land use types (farm, hoop pine plantation and two open eucalyptus forests, including one with a triennial fire regime) to parameterise the weed's vital rates and develop size‐structured matrix models. Lantana camara in its re‐colonization phase, as observed in the recently cleared hoop pine plantation, was projected to increase more rapidly (annual growth rate, λ = 3.80) than at the other three sites ( λ 1.88–2.71). Elasticity analyses indicated that growth contributed more (64.6 %) to λ than fecundity (18.5 %) or survival (15.5 %), while across size groups, the contribution was of the order: juvenile (19–27 %) ≥ seed (17–28 %) ≥ seedling (16–25 %) > small adult (4–26 %) ≥ medium adult (7–20 %) > large adult (0–20 %). From a control perspective it is difficult to determine a single weak point in the life cycle of lantana that might be exploited to reduce growth below a sustaining rate. The triennial fire regime applied did not alter the population elasticity structure nor resulted in local control of the weed. However, simulations showed that, except for the farm population, periodic burning could work within 4–10 years for control of the weed, but fire frequency should increase to at least once every 2 years. For the farm, site‐specific control may be achieved by 15 years if the biennial fire frequency is tempered with increased burning intensity.